Properties of Concrete Containing Mussel (Perna viridis) Shell Ash as Partial Cement Replacement - Sainudin, Muhammad Shabery (International Journal of Integrated Engineering, 2019)
This paper present data on physical, chemical and engineering properties of concrete such as compressive and spilt tensile strength using mussel shell ash (MSA) (Perna viridis) as partial cement replacement. Samples of concrete were mixed with different proportions of 0%, 3%, 5% and 7% (S0, S3, S5 & S7) MSA with target strength of 35 MPa on day 28. The samples were cured in water for 7, 28 and 60 days. The properties of MSA were identified through tests including X-Ray Fluorescence (XRF), setting time, particle size distribution (PSD), specific gravity and scanning electron microscopy (SEM). The results showed that the specific gravity of MSA was lower compared to cement while the XRF test showed that the content of calcium oxide (CaO) in mussel shell ash (71.5%) was higher than that of Portland cement (57.2%). The initial and final setting time for the cement paste became shorter when the percentage of MSA increased. From the observation of the microstructure analysis, the SEM test showed that there was a significant increase in calcium hydroxide (CH) content along with the increment in mussel shell ash content in concrete. The strength tests (compressive strength and tensile strength) were carried out and analyzed in terms of correlation. It was found that mussel shell ash influenced the strength of concrete especially for concrete containing 3% mussel shell ash as a partial cement replacement (S3).